Modern therapeutic criteria for breast cancers - Valls, Alberto; Asiner, Boris; Mayol, Ricardo (Cirugía del Uruguay, 1979)
The authors describe the new therapeutic concept of mammary cancer consisting in inmunologic factors, early detection by means of X - rays, diaphanography and cytologic puncture, as well as a more correct diagnosis of extension of neoplasia by means of enzymogramme and liver scanning and scanning of bone structure with pyrophosphate technetium. PEV classification of G. Roussy Institute (Paris) is described- Series consists of 4 cases.